Preparation of Paclitaxel Liposome and its Anticancer Activity - Luo, Yingquan; Yang, Yu; Zhang, Hui; Zhang, Ting; Wang, Yina; Tan, Shengyu; Xu, Yan; Li, Dan; Ye, Ling; Chen, Ping (Asian Journal of Chemistry, 2014)
The aim of the study was to study the preparation process of paclitaxel liposome and to determine its anticancer effect. Orthogonal experiment was used to study the preparation process of paclitaxel liposome and MTT assay was used to determine its anticancer effect. Factors influencing the encapsulation efficiency of paclitaxel liposome in order of importance were: B > A > C, i.e. the ratio of hydrogenated phospholipid to paclitaxel > the weight ratio of phospholipid to cholesterol > rotary evaporation temperature. It can be seen from the results of range analysis that under the experimental conditions, the optimal preparation process of paclitaxel liposome was A3B1C3, i.e. the phospholipid to cholesterol weight ratio of 20:4.28, hydrogenated phospholipid to paclitaxel weight ratio of 20:1 and rotary evaporation temperature of 60 °C. Different concentrations of paclitaxel liposomes (0.05, 0.1, 0.5 and 1 μmol/L) all had significant inhibitory effects on SGC-7901 cells and within a certain dose range, the inhibitory effects gradually increased with the increase of drug concentration in culture medium and the extension of incubation time, of which 1 μmol/L paclitaxel liposome had the strongest inhibitory effect on SGC-7901 cells at 72 h, reaching 75.9 %. Paclitaxel liposome can effectively inhibit the proliferation of SGC-7901 cells.